3D Cf/SiC-ZrC-ZrB2 composites fabricated via sol-gel process combined with reactive melt infiltration. Issue 15 (November 2016) - Chen, Xiaowu; Dong, Shaoming; Kan, Yanmei; Zhou, Haijun; Hu, Jianbao; Wang, Dengke
Abstract: Three-dimensional (3D) Cf /SiC-ZrC-ZrB2 composites were successfully fabricated by sol-gel process combined with reactive melt infiltration (RMI) method. With H3 BO3 and PVA as raw materials for gel precursor, a porous C-B4 C matrix was first introduced into the 3D carbon fiber preform by impregnation of the gel precursor, followed by heat-treatments of pyrolysis and carbothermal processes at 1500 °C in Ar atmosphere. Then molten ZrSi2 alloys were infiltrated into the 3D Cf /C-B4 C preform to obtain 3D Cf /SiC-ZrC-ZrB2 composites. Based on thermodynamic analysis, the formation mechanism of SiC-ZrC-ZrB2 matrix was revealed. Oxidation resistance and ablation resistance properties of the fabricated 3D Cf /SiC-ZrC-ZrB2 composites were tested using a muffle furnace and a plasma wind tunnel equipment, respectively. The flexural strength of the as prepared composites and its strength retention after oxidation were evaluated. It is revealed that the 3D Cf /SiC-ZrC-ZrB2 composites showed superior flexural strength, good oxidation resistance and excellent anti-ablation properties.